Determination of Cr(VI) and Cr(III) in water using activated carbon-atomic absorption spectrometry - Yaman, M (Editura Acad Romane, 2003)
A method for the determination of Cr(VI) and Cr(III) in synthetic aqueous solutions was examined. Adsorption on activated carbon was carried out to separate Cr(VI) from Cr(III) and preconcentrate Cr(VI) using NaDDTC as complexing reagent. The factors such as composition of buffer solution, pH, temperature, amounts of the used reagents and stirring time were examined and optimised. The proposed method allows determination and separation of very low levels of Cr(VI) and Cr(III). The optimised method was applied to the natural water and the synthetic solutions containing Cr(VI) of 40 mug L-1 and Cr(III) of 10 mug L-1.
Keywords: Natural-Waters; Chromium(Vi); Preconcentration; Enrichment; Matrices; Vegetables; Separation; Extraction; Vanadium; Cadmium